Transgenic insect-resistant Bt cotton expressing Cry1Ac/CpTI does not affect the mirid bug Apolygus lucorum. (September 2020) - Niu, Lin; Liu, Fang; Zhang, Shuai; Luo, Junyu; Zhang, Lijuan; Ji, Jichao; Gao, Xueke; Ma, Weihua; Cui, Jinjie
Abstract: Common varieties of genetically modified (GM) cotton increasingly display insect-resistant properties via expression of bacterial-derived toxins from Bacillus thuringiensis (Bt). This necessitates a deeper understanding of the possible effects of these crops on non-target insects. The mirid bug Apolygus lucorum is a major pest in cotton production in China, however, the effect of GM cotton on this non-target species is currently virtually unknown. This insect is exposed to these transgenic plants by consuming genetically modified (GM) leaves. In this study, laboratory experiments were conducted to assess the toxicity of CCRI41 and CCRI45, (genetically modified cotton varieties which express the toxins Cry1Ac and CpTI (Cowpea Trypsin Inhibitor)) on nymphs and adults of A. lucorum . There was no detectable increase in mortality after A. lucorum fed on GM cotton leaves for 20 days. While we detected trace amounts of Cry1Ac proteins in both A. lucorum nymphs and adults (<10 ng/g fresh weight), the expression of genes related to detoxification did not detectably differ from those feeding on non-GM cotton. Our binding assays did not show Cry1Ac binding to receptors on the midgut brush border membrane from either A. lucorum nymphs or adults. Our findings collectively indicate that feeding on leaves of the GM cotton varieties CCRI41 and CCRI45 have few toxic effects on A. lucorum . Graphical abstract: Image 1 Highlights: Bioassay results showed no effect of Cry1Ac -expressing cotton on Apolygus lucorum survival rate . Cry1Ac -expressing cotton did not alter the detoxification genes expression of A. lucorum. No cry1Ac binding protein was detected in the midgut of A. lucorum. Planting transgenic Cry1Ac cotton will pose a negligible risk to A. lucorum. Abstract : Capsule: Our study indicated that the GM cotton varieties CCRI41 and CCRI45 have few adverse effects on non-target insect pest A. lucorum .